Members of the tomato NRC4 h-NLR family augment each other in promoting basal immunity. (May 2023) - Leibman-Markus, Meirav; Gupta, Rupali; Schuster, Silvia; Avni, Adi; Bar, Maya
Abstract: Plants possess an efficient, two-tiered immune system to combat pathogens and pests. Several decades of research have characterized different features of these two well-known tiers, PTI and ETI (Pattern/ Effector-triggered Immunity). NLR (Nucleotide-binding domain Leucine-rich Repeat) receptors have been found to link PTI to ETI, and be required for full potentiation of plant immune responses in several systems. Intra-cellular helper-NLRs (h-NLRs) mediate ETI and have been focused on extensively in recent research. Previously, we investigated the roles of the h-NLR SlNRC4a in tomato immunity, finding that a specific mutation in this gene results in gain of function constitutive defense activation and broad disease resistance. Deletion of the entire NRC4 clade, which contains 3 genes, can compromise tomato immunity. Here, we decided to investigate the role of an additional clade member, SlNRC4b, in basal immunity. We generated a gain of function mutant in SlNRC4b using CRISPR-Cas9, as well as a double gain of function mutant in both genes. Similarly to the slnrc4a mutant, a slnrc4b mutant also possessed increased basal immunity and broad spectrum disease resistance. The double mutant displayed additive effects in some cases, with significant increases in resistance to fungal phytopathogens as compared with each of the single mutants. Our work confirms that the NRC4 family h-NLRs are important in the plant immune system, suggesting that this gene family has the potential to be promising in targeted agricultural adaptation in the Solanaceae family, promoting disease resistance and prevention of yield loss to pathogens. Highlights: h-NLR receptors mediate ETI and link ETI to PTI within the plant immune system. A gain of function mutation in the h-NLR SlNRC4a activates defense constitutively. Here, we investigated the role of  SlNRC4b  in basal immunity. A slnrc4b mutant possessed increased basal immunity and disease resistance. The double slnrc4a/b mutant displayed additive effects. The NRC4 family shows promise for targeted agricultural adaptation for disease resistance.